Integrated management of chocolate spot (Botrytis fabae Sard) through host resistance and fungicide application in the highlands of Bale, Southeastern Ethiopia - Ermias Teshome; Dagne Kora (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2021)
Because of its nutritional value, Faba bean (Vicia faba L.) is one of the most important food legumes both as energy and protein source. It is among the most important pulse crops produced in Ethiopia in general and on the highlands of Bale in particular. Field experiment was conducted at Sinana Agricultural Research Center on-station using RCBD with three replications to study the integrated effect of fungicide (sprayed at various frequencies) and faba varieties to manage chocolate spot. The experiment consisted of five (5) fungicide application frequencies and two Faba bean varieties (Gebelcho and Mosisa). Logistic model, [ln [(Y/1-Y)] was used to calculate the disease parameters such as disease progress rate (r) and AUDPC. The partial budget analysis was carried out to asses financial profitability of fungicide application for the management of chocolate spot. ANOVA showed statistically significant difference (P<0.05) among the treatments for the disease parameters. The lowest chocolate spot severity (23.15%) and the best chocolate spot disease control was achieved from Gebelcho variety sprayed four times. Similarly, the lowest r (-0.00453units/day) and AUDPC (823.1 %-days) were recorded from Gebelcho variety sprayed four times. Regarding yield and yield components, ANOVA showed significant differences (P<0.05) among the treatments. The highest number of pods per plant (15.28) was recorded from Gebelcho variety sprayed 2 times whereas, the highest TKW of 662.60 g was recorded from Gebelcho variety sprayed three times. In terms of grain yield, the maximum grain yield of 3515.44 kg/ha was obtained from Mosisa variety sprayed four times and four times spray of Gebelcho variety gave the second highest grain yield of 3313.70kg/ha. Partial budget analysis has shown the maximum marginal benefit of 41044.8ETBha-1 obtained from Mosisa variety sprayed four times at weekly interval while the second marginal benefit of 38624.4ETBha-1was obtained from Gebelcho variety sprayed four times at weekly interval. The maximum MRR of 1726.11 % was obtained from Mosisa variety sprayed once and the second highest MRR (1592.84 %) was calculated from Gebelcho variety sprayed four times. Therefore, the recommendation is made depending on the results from the biological studies and partial budget analysis. For small scale farmers, it is recommended to produce Mosisa variety by spraying mancozeb 80% WP once to maximize the financial benefit from faba bean production. But, for small scale farmers who can afford, it is recommended to produce faba bean variety Mosisa sprayed three times by a fungicide mancozeb 80%. However, for large scale farmers who are producing faba bean for export market are recommended to produce faba bean variety Gebelcho sprayed four times at 7-10 days interval.